Exotic foods reveal contact between South Asia and the Near East during the second millennium BCE - Scott, Ashley; Power, Robert C.; Altmann-Wendling, Victoria; Artzy, Michal; Martin, Mario A. S.; Eisenmann, Stefanie; Hagan, Richard; Salazar-García, Domingo C.; Salmon, Yossi; Yegorov, Dmitry; Milevski, Ianir; Finkelstein, Israel; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Although the key role of long-distance trade in the transformation of cuisines worldwide has been well-documented since at least the Roman era, the prehistory of the Eurasian food trade is less visible. In order to shed light on the transformation of Eastern Mediterranean cuisines during the Bronze Age and Early Iron Age, we analyzed microremains and proteins preserved in the dental calculus of individuals who lived during the second millennium BCE in the Southern Levant. Our results provide clear evidence for the consumption of expected staple foods, such as cereals (Triticeae), sesame (Sesamum), and dates (Phoenix). We additionally report evidence for the consumption of soybean (Glycine), probable banana (Musa), and turmeric (Curcuma), which pushes back the earliest evidence of these foods in the Mediterranean by centuries (turmeric) or even millennia (soybean). We find that, from the early second millennium onwards, at least some people in the Eastern Mediterranean had access to food from distant locations, including South Asia, and such goods were likely consumed as oils, dried fruits, and spices. These insights force us to rethink the complexity and intensity of Indo-Mediterranean trade during the Bronze Age as well as the degree of globalization in early Eastern Mediterranean cuisine.
Gesehen am 23.06.2021